The interdependent, overlapping and differential roles of type I and type II interferons in the pathogenesis of experimental autoimmune encephalomyelitis() - Naves, Rodrigo (2013)
Type I IFNs (IFN-α and IFN-β) and type II IFN (IFN-γ) mediate both regulation and inflammation in multiple sclerosis (MS), neuromyelitis optica (NMO) and in experimental autoimmune encephalomyelitis (EAE). However the underlying mechanism for these Janus-like activities of type I and II IFNs in neuroinflammation remains unclear. Although endogenous type I IFN-signaling provides a protective response in neuroinflammation, we find that when IFN-γ signaling is ablated, type I IFNs drive inflammation resulting in exacerbated EAE. IFN-γ has disease stage-specific opposing function in EAE. Treatment of mice with IFN-γ during initiation phase of EAE leads to enhanced severity of disease. In contrast, IFN-γ treatment during effector phase attenuated disease. This immunosuppressive activity of IFN-γ required functional type I IFN-signaling. In IFN-α/β receptor (IFNAR) deficient mice, IFN-γ treatment during effector phase of EAE exacerbated disease. Using an adoptive transfer-EAE model, we found that T-cell intrinsic type I and type II IFN signals are simultaneously required to establish chronic EAE by encephalitogenic Th1 cells. However in Th17 cells loss of either IFN signals leads to the development of a severe chronic disease. The data implies that type I and type II IFN signals have independent but non-redundant role in restraining encephalitogenic Th17 cells in vivo. Overall our data show that type I and type II IFNs function in an integrated manner to regulate the pathogenesis in EAE.